Carbonic Anhydrase Activities from the Rainbow Trout Lens Correspond to the Development of Acute Gas Bubble Disease - Ateş, Orhan; Gültepe, Nejdet; Beydemi̇r, Şükrü; Hi̇sar, Olcay (Oxford University Press (OUP), 2011)
Abstract Dissolved gas supersaturation is hazardous to fish and can result in gas bubble disease (GBD). Signs of GBD typically include bubbles in the eyes, fins, skin, lateral line, and gill filaments. Ocular abnormalities in diseased salmonids typically occur after aberrant gas production in the eyes. In this study, freshwater rainbow trout Oncorhynchus mykiss were exposed experimentally to percent total gas pressure (TGP%) levels of 104% (control) and 115%. No mortalities occurred during the 7-d experimental period. Effects of GBD were observed externally as a darkened skin, exophthalmia, localized hemorrhage in the eye, and gas bubbles on the operculum. Additional signs included increased swimming activity and, more frequently, panic episodes. Carbonic anhydrase (CA) enzyme activities from the lens and retina were determined at days 0, 1, 3, 5, and 7 of the study. Venous blood gases were also measured on day 7. Retinal pH did not differ between normal and affected fish, but blood characteristics such as the partial pressure of O2, partial pressure of CO2, carboxyhemoglobin level, and bicarbonate ion concentration were significantly elevated in affected fish relative to normal fish. Venous blood pH and oxyhemoglobin levels were not significantly different between affected and normal fish. Patterns of response to total dissolved gas levels differed between the lens and the retina. Mean CA activities in the lenses of fish exposed to a TGP% level of 115% were significantly below those of control fish. However, retinal CA activities did not significantly differ between the two groups over the course of the experiment. These findings show that dissolved gas supersaturation reduces CA activity in the rainbow trout lens. Received June 17, 2010; accepted March 20, 2011
Keywords: Fish Diseases; Oncorhynchus mykiss; Animals; Embolism, Air; Water; Carbonic Anhydrases; 14. Life underwater